QUO VADIS AKUNTAN DALAM ERA REVOLUSI INDUSTRI 4.0 - Rista Upa Tikurante; Oktavianus Pasoloran; Sita Yubelina Sabandar (Program Studi Akuntansi Universitas Kristen Indonesia Paulus, 2020)
The purpose of this study is to understand the readiness of the accounting profession and determine the opportunities and challenges of the accounting profession in the industrial revolution 4.0. This research uses a descriptive qualitative method and interview techniques to collect the data. The interview was used for public accountants, professional accountant and educator accountants. The results of this study indicate that the industrial revolution 4.0 requires the accountants to adapt to the development of information technology. The role of accountants today is no longer limited to book-keeping. However, it includes internal control, providing information analysis for management, especially related to the company's financial strategies. Accountants must be able to transform into information technology because in the 4.0 industrial revolution the use of technology has increased. In addition, accountants must equip themselves with non-accounting aspects, so that they have advantages in addition to financial aspects.